2009
DOI: 10.1152/ajpregu.90506.2008
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine, oxidative stress, and vascular nitric oxide synthase in essential hypertension

Abstract: -We reported impaired endotheliumderived relaxation factor/nitric oxide (EDRF/NO) responses and constitutive nitric oxide synthase (cNOS) activity in subcutaneous vessels dissected from patients with essential hypertension (n ϭ 9) compared with normal controls (n ϭ 10). We now test the hypothesis that the patients in this study have increased circulating levels of the cNOS inhibitor, asymmetric dimethylarginine (ADMA), or the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid (HODE), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 49 publications
3
59
0
2
Order By: Relevance
“…148 Additionally, normotensive subjects with a family history of hypertension have greater H 2 O 2 production than blood pressure-matched normotensives without a family history of hypertension, suggesting that there may be a genetic component that leads to elevated production of H 2 O 2 . 149,150 Plasma levels of asymmetric dimethylarginine (endothelial nitric oxide synthase inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. To further support a relationship between oxidative stress and blood pressure, Van et al 151 recently showed that myeloperoxidase is positively and independently associated with blood pressure and that this association is strongest in subjects with increased levels of oxidative markers.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…148 Additionally, normotensive subjects with a family history of hypertension have greater H 2 O 2 production than blood pressure-matched normotensives without a family history of hypertension, suggesting that there may be a genetic component that leads to elevated production of H 2 O 2 . 149,150 Plasma levels of asymmetric dimethylarginine (endothelial nitric oxide synthase inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. To further support a relationship between oxidative stress and blood pressure, Van et al 151 recently showed that myeloperoxidase is positively and independently associated with blood pressure and that this association is strongest in subjects with increased levels of oxidative markers.…”
Section: Ros and Vascular Biology In Hypertensionmentioning
confidence: 99%
“…Кроме того, перегрузка ЛЖ давлением, нарушения диастолической функции ЛЖ приводят к перегрузке ЛП и сопровождаются увеличением его размера, который у пациентов с РАГ стремится к предельным значениям, достижение которого увеличивает риск развития фибрилляции предсердий [20]. Таким об-разом, у пациентов с резистентной артериальной ги-пертензией отмечается сформировавшаяся, прогно-стически наиболее неблагоприятная концентрическая гипертрофия миокарда левого желудочка, что является наиболее значимым фактором риска сердечно-со-судистых осложнений, в том числе со смертельным исходом [21,22]. Огромную роль в развитии не-обратимых изменений в миокарде при АГ в виде его гипертрофии ЛЖ и интерстициального фиброза иг-рает состояние МЦР.…”
Section: Discussionunclassified
“…In order that increased level of ADMA can have the important role in the pathogenesis of atherosclerosis and E-ARMD. [10][11][12][13][14] Dimethylarginine dimethylaminohydrolase (DDAH) is an enzyme that it degrades methylarginine, specifically ADMA. The activity of DDAH is impaired by oxidative stress, permitting ADMA to accumulate.…”
mentioning
confidence: 99%
“…11,15,27,28 High level of ADMA can also induce oxidative damage in vascular tissues results in endothelial dysfunction. 10,12 Endothelial function depends on the integrity of constitutive NOS and the availability and vascular signaling of its product, NO. 12 Vallance et al 29 reported a large increase in serum concentrations of ADMA in patients with CKD and end-stage renal disease and showed that ADMA inhibited NOS and that ADMA and cationic amino acid transferase.…”
mentioning
confidence: 99%
See 1 more Smart Citation